solve this sums maths sums
Attachments:
![](https://hi-static.z-dn.net/files/dbc/338bdbce60ff1ca81cdf486c55b7afaa.jpg)
Answers
Answered by
5
Answer:
x= -1
x= -1.5
Step-by-step explanation:
- 2x/(x-3)+1/(2x+3)+(3x+9)/(x-3)(2x+3)=0
- {2x(2x+3)+(x-3)+3x+9)}/(x-3)(2x+3)=0
- 4x²+6x+x-3+3x+9=0
- 4x²+10x+6=0
- 2x²+5x+3=0
- x= -1, x= -1.5
Answered by
6
ANSWER
x= -1
x= -1.5
step by step
2x/(x -3)+ 1/(2x +3)+ (3x +9)/(x -3)(2x +3)=0
{2x(2x+3)+(x-3)+3x+9)}/(x-3)(2x+3)=0
4x²+6x+x-3+3x+9=0
4x²+10x+6=0
2x²+5x+3=0
x= -1,x= -1.5
Similar questions